Composition and Morphology of Nanocrystals in Urines of Lithogenic Patients and Healthy Persons. (27th September 2009) - Gui, Bao-Song; Xie, Rong; Yao, Xiu-Qiong; Li, Mei-Ru; Ouyang, Jian-Ming
Abstract : The composition and morphology of nanocrystals in urines of healthy persons and lithogenic patients were comparatively investigated by means of X-ray diffraction (XRD) and transmission electron microscopy (TEM). It was shown that the main composition of urinary nanocrystals in healthy persons were calcium oxalate dihydrate (COD), uric acid, and ammonium magnesium phosphate (struvite). However, the main compositions of urinary nanocrystals in lithogenic patients were struvite, β -tricalcium phosphate, uric acid, COD, and calcium oxalate monohydrate (COM). According to the XRD data, the size of nanocrystals was calculated to be23 ∼ 72 nm in healthy urine and12 ∼ 118 nm in lithogenic urine by Scherer formula. TEM results showed that the nanocrystals in healthy urine were dispersive and uniform with a mean size of about 38 nm. In contrast, the nanocrystals in lithogenic urine were much aggregated with a mean size of about 55 nm. The results in this work indicated that the urinary stone formation may be prevented by diminishing the aggregation and the size differentiation of urinary nanocrystals by physical or chemical methods.